Immunological features of T cells induced by human telomerase reverse transcriptase-derived peptides in patients with hepatocellular carcinoma. Issue 2 (10th August 2015) - Mizukoshi, Eishiro; Nakagawa, Hidetoshi; Kitahara, Masaaki; Yamashita, Tatsuya; Arai, Kuniaki; Sunagozaka, Hajime; Fushimi, Kazumi; Kobayashi, Eiji; Kishi, Hiroyuki; Muraguchi, Atsushi; Kaneko, Shuichi
Highlights: The safety and immunogenicity of hTERT-derived peptide (hTERT461 ) as a peptide vaccine to hepatocellular carcinoma was confirmed. The post-vaccinated increase in hTERT461 peptide-specific T cells was due to the increase in cells with the effector memory phenotype. We showed the possible efficacy of hTERT-derived peptide vaccine in preventing HCC recurrence after curative treatments. We also succeeded in obtaining the hTERT-specific T cell receptors from hTERT461 peptide-specific T cells. Abstract: Human telomerase reverse transcriptase (hTERT) is a catalytic enzyme required for telomere elongation. In this study, we investigated the safety and immunogenicity of an hTERT-derived peptide (hTERT461 ) as a vaccine and characterized the hTERT-specific T cell responses induced. Fourteen hepatocellular carcinoma (HCC) patients were enrolled in the study. The hTERT-derived peptide was emulsified in incomplete Freund's adjuvant and administered via subcutaneous immunization three times biweekly. The maximum toxicity observed was grade 2 according to the common terminology criteria and mainly consisted of skin reactions at the site of vaccination. The vaccination induced hTERT-specific immunity in 71.4% of patients and 57.1% of patients administered with hTERT461 peptide-specific T cells could prevent HCC recurrence after vaccination. In phenotypic analysis, the post-vaccinated increase in hTERT-specific T cells was due to an increase in cells with the effector memory phenotype, with the potential to produce multiple cytokines. Seven hTERT-specific T cell receptors were obtained from the vaccinated patients, showing their cytotoxic activities to hTERT-derived peptide-bearing cells. In conclusion, the safety and effects of immune boosting by hTERT461 peptide have shown the potential of the peptide to provide clinical benefits in HCC patients.